Out-of-pocket health expenditure and associated factors among patients with hypertension in Debre-Tabor Comphrensive Specialized Hospital, South Gondar zone, Northwest Ethiopia, 2020 - Alemayehu, Melkamu; Addis, Banchlay; Hagos, Tsega (Frontiers in Public Health, 2023)
Introduction: - Hypertension is a non-communicable chronic disease that has a wide financial effect at the individual and household levels especially in developing countries due to its complexity and chronicity. Nevertheless, there are limited studies in Ethiopia. Therefore the aim this study was to assess out-of-pocket health expenditure and associated factors among adult patients with hypertension in Debre-Tabor General Hospital. Methods: - A facility-based cross-sectional study was conducted in total of 357 adult hypertensive patients from February to March 2020 using a systematic random sampling technique. Descriptive statics were used to estimate the magnitude of out of pocket health expenditure, while after checking the assumptions linear regression model was fitted for identifying the factors associated with the outcome variable at a significance level of p-value < 0.05 and 95% confidence interval. Result: -A total of 346 study participants interviewed with a response rate of 96.92%. Annual mean out of pocket health expenditure of the participant was 113.40 ± 101.82 with 95% CI= (102.63, 124.16) per patient. The direct medical mean out of pocket health expenditure of the participant was 68.86 per patient per year and the median of non-medical components of the out of pocket health expenditure of the participant was 3.53. Sex, wealth status, distance from hospital, comorbidity, health insurance and number of visit are factors significantly associated to out of pocket expenditure. Conclusion: This study revealed that out-of-pocket health expenditure among adult patients with hypertension was found high compared to the national per capita health expenditure. Sex, wealth index, distance away from hospital, frequency of visit, comorbidities, and health insurance coverage were factors significantly associated with high out-of-pocket health expenditure. Ministry of health together with regional health bureaus and other concerned stakeholders work on strengthening early detection and prevention strategies of chronic comorbidities of hypertensive patients and better to subsidize medication costs.